Pemanfaatan Aplikasi Sistem Pendataan Anggota UMKM Paguyuban (THB) Kota Bekasi - Ahas Eko Septianto; Dede Sulaiman; Andi Febrianto Sutisna (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The UMKM Association of Bekasi City has challenges in collecting data on members of micro, small and medium enterprises (MSMEs) in Taman Harapan Baru RW 23, Pejuang Village, Medan Satria District, Bekasi City. Limitations in making periodic reports cause difficulties for cooperatives in providing accurate MSME member data information to the MSME Cooperative Service. To overcome this problem, we developed a computer and database system that would make data collection easier. This system enables efficient and easy monitoring of member data, considering the large number of members who are members of the community. Through community service activities, we have succeeded in producing a website application that uses JavaScript programming language technology with the Next.js Library and the MongoDB database. This application assists the community in collecting data and searching for member data, as well as creating member business identities through online cards that can be accessed from anywhere via the internet. The information system that has been developed provides a solution to improve the efficiency and accuracy of data collection for MSME members, as well as facilitating easier access to information for related parties, such as the MSME Cooperative Office. With this website application, UMKM Paguyuban Kota Bekasi can carry out data collection activities more effectively and efficiently. In addition, the information system that has been developed can also support data-based decision making for MSME empowerment programs in the region.